monte carlo simulation in the kinetics and mileculare - Baghdad Science Journal (Baghdad Science Journal, 2006)
The primary focus of the study factor reverse polymerization styrene polymer kinetics and distribution weight Aljaia in Blma Aldhur free reverse The study was conducted wi Mamahakah and using the Monte Carlo method